Transformasi Kepemimpinan dalam Kemandirian Ekonomi melalui Kewirausahaan di Pesantren Mambaul Ulum Al-Murtadlo Tiris - Qomariyah; Misbahul Arifin; Abdullah (Educational Research Center, 2026)
Islamic educational institutions in Indonesia are facing increasing challenges in maintaining institutional sustainability due to heavy reliance on conventional funding sources and the weak integration of entrepreneurial management systems. This situation calls for leadership transformation that goes beyond academic administration and normative values toward a more strategic response to economic sustainability. This study aims to analyze how leadership transformation in Islamic educational institutions contributes to the development of entrepreneurial management as a strategy for economic self-reliance. The research employed a qualitative approach with a case study design conducted at Mambaul Ulum Al-Murtadlo Islamic Boarding School in Probolinggo Regency. Data were collected through in-depth interviews, limited participatory observation, and document analysis, and analyzed using Miles and Huberman’s interactive data analysis model. The findings reveal that leadership transformation has shifted leaders’ orientations from routine administrative roles to visionary and strategic leadership, resulting in more systematic, accountable, and institutionally integrated entrepreneurial management. Moreover, entrepreneurship was not found to undermine Islamic values; instead, it strengthened the moral legitimacy of economic practices within the institution. The study implies that transformative leadership is a crucial foundation for strengthening economic independence and ensuring the long-term sustainability of Islamic educational institutions.